APLIKASI MANAJEMEN SURAT MASUK DAN SURAT KELUAR BERBASIS MOBILE DI SEKRETARIAT DAERAH KABUPATEN SUKABUMI - ridwan yus (Jurnal Teknologi Informatika dan Rekayasa Terapan, 2026)
The management of incoming and outgoing mail is a crucial part of office administration, including at the Regional Secretariat of Sukabumi Regency. Currently, the process of recording and archiving letters is often still conducted conventionally, which poses risks such as delays in data retrieval and potential damage to physical documents. This study aims to develop a mobile-based mail management application named SiSuMaker (Sistem Surat Masuk dan Keluar). The application was developed using the Dart programming language with the Flutter framework and a permanent data storage system. Key features include profile management, data input for incoming and outgoing mail, and automatic data recapitulation to facilitate real-time archive monitoring. The results of this development are expected to improve efficiency, data security, and the speed of information access in mail management within the local government environment.